The effects of pterostilbene on neutrophil activity in experimental model of arthritis - Perecko, Tomas; Drabikova, Katarina; Lojek, Antonin; Ciz, Milan; Ponist, Silvester; Bauerova, Katarina; Nosal, Radomir; Harmatha, Juraj; Jancinova, Viera (BioMed research international, 2013)
It has been demonstrated that pterostilbene inhibits reactive oxygen species production in neutrophils in vitro. However, little is known about its effects on neutrophils during inflammation in vivo. In this study, the effect of pterostilbene on neutrophil activity was investigated in experimental arthritis model. Lewis rats were injected by a single intradermal injection of heat-killed Mycobacterium butyricum in Freund's adjuvant to develop arthritis. Another group of arthritic animals received pterostilbene 30 mg/kg, daily, p.o. The number and activity of neutrophils in blood were measured on a weekly basis during the whole experiment. Moreover, the total radical trapping potential in plasma was measured at the end of the experiment. In the pterostilbene treated arthritic group, the treatment significantly lowered the number of neutrophils in blood on days 14 and 21 without significant downregulation of neutrophil oxidative burst. Pterostilbene nonsignificantly increased total radical trapping potential in arthritic animals. These results indicate that the promising effects of pterostilbene on reactive oxygen species operate by different mechanisms in vitro and in the animal model of inflammation. In conclusion, the positive effects of pterostilbene in the model of arthritis may be attributed to regulation of neutrophil number.
Keywords: Animals; potkani inbrední LEW; Peroxides; Cross-Priming; nepřímá aktivace; peroxidy; stilbeny; počet leukocytů; Stilbenes; Reactive Oxygen Species; Down-Regulation; Leukocyte Count; Male; Arthritis, Experimental; modely nemocí na zvířatech; Neutrophils; Disease Models, Animal; neutrofily; reaktivní formy kyslíku; krysa rodu Rattus; down regulace; zvířata; mužské pohlaví; artritida experimentální; Rats, Inbred Lew; Rats